Ζ1 + ζ2 Reticuli binary system: a puzzling chromospheric activity pattern. Issue 2 (20th March 2018) - Flores, M; Saffe, C; Buccino, A; Jaque Arancibia, M; González, J F; Nuñez, N E; Jofré, E
Abstract: We perform, for the first time, a detailed long-term activity study of the binary system ζ Ret. We use all available HARPS spectra obtained between the years 2003 and 2016. We build a time series of the Mount Wilson S index for both stars, then we analyse these series by using Lomb–Scargle periodograms. The components ζ 1 Ret and ζ 2 Ret that belong to this binary system are physically very similar to each other and also similar to our Sun, which makes it a remarkable system. We detect in the solar-analogue star ζ 2 Ret a long-term activity cycle with a period of ∼10 yr, similar to the solar one (∼11 yr). It is worthwhile to mention that this object satisfies previous criteria for a flat star and for a cycling star simultaneously. Another interesting feature of this binary system is a high ∼0.220 dex difference between the average (R^′ _HK ) activity levels of both stars. Our study clearly shows that ζ 1 Ret is significantly more active than ζ 2 Ret. In addition, ζ 1 Ret shows an erratic variability in its stellar activity. In this work, we explore different scenarios trying to explain this rare behaviour in a pair of coeval stars, which could help to explain the difference in this and other binary systems. From these results, we also warn that for the development of activity–age calibrations (which commonly use binary systems and/or stellar clusters as calibrators) the whole history of activity available for the stars involved should be taken into account.